MALDI TOF Mass Spectrometry Imaging of Blood Smear: Method Development and Evaluation - Željko Debeljak (International Journal of Molecular Sciences, 2021)
The aim of this study was to develop and evaluate matrix assisted LASER desorption ionization (MALDI) time-of-flight (TOF) mass spectrometry imaging (MSI) of blood smear. Integrated light microscope and MALDI IT-TOF mass spectrometer, together with a matrix sublimation device, were used for analysis of blood smears coming from healthy male donors. Different blood plasma removal, matrix deposition, and instrumental settings were evaluated using the negative and positive ionization modes while agreement between the light microscopy images and the lateral distributions of cellular marker compounds served as the MSI quality indicator. Red and white blood cells chemical composition was analyzed using the differential m/z expression. Five seconds of exposure to ethanol followed by the 5 min of 9-aminoacridine or α-cyano-4-hydroxycinnamic acid deposition, together with two sets of instrumental settings, were selected for the MALDI TOF MSI experiments. Application of the thin and transparent matrix layers assured good correspondence between the LASER footprints and the preselected regions of interest. Cellular marker m/z signals coincided well with the appropriate cells. A metabolite databases search using the differentially expressed m/z produced hits which were consistent with the respective cell types. This study sets the foundations for application of blood smear MALDI TOF MSI in clinical diagnostics and research.